The Effect of Workload, Social Support and Role Conflict on Work Stress That Impacts Work Performance at SMA Santo Yoseph, Cakung - Siahaan, Rahel Sintadevi; Rudianto, Rudianto; Rante, Jones Zenas; Pakpahan, Marisi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study investigates the effects of workload, social support, and role conflict on work stress and its subsequent impact on teacher performance at SMA Santo Yoseph, Cakung. A quantitative approach was adopted, employing a census method involving 24 teachers. Data were analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) technique through SmartPLS version 4.1.0.9. The outer model analysis confirmed that all constructs met the criteria for convergent validity and internal consistency reliability (CR > 0.7). The inner model evaluation revealed adjusted R² values of 0.812 for work stress and 0.774 for job performance, along with Q² values exceeding 0.5, indicating strong predictive relevance. Hypothesis testing demonstrated that workload (β = 0.392; p < 0.05) and role conflict (β = 0.327; p < 0.05) exert a significant positive influence on work stress, whereas social support has a significant negative effect (β = -0.321; p < 0.05). Furthermore, work stress significantly reduces job performance (β = -0.509; p < 0.05). Both workload and role conflict were found to have direct negative effects on job performance. While social support and work stress were also shown to influence performance positively, the effect of work stress, although significant, was relatively weak. Nevertheless, the analysis of indirect effects indicated that work stress does not mediate the relationships between workload, social support, and role conflict with job performance, as all three indirect paths were statistically insignificant. The findings underscore the importance of managing workload and role conflict, as well as fostering social support within the school environment, to enhance teacher performance. Additionally, moderate levels of work stress (eustress) may serve as a performance enhancer, provided it is managed to avoid escalation into harmful distress..